Promoting inquiry method module using ICT in learning grammar in ESL classroom among form 2 students in Pahang / Azurawati Wok Zaki - Wok Zaki, Azurawati (2014)
The movement to upgrade basic education and improve its quality is now very much on the programme of many countries including the developing ones. Meaning that, there is an implication, there is an overwhelming concern over the quality and relevance of education globally. Undoubtedly, the quality of education depends on the method used in the lesson. Suffice it to note the importance of inquiry in the learning grammar process, as, allowing students to ask questions, construct explanations, test those explanations against current knowledge, and communicate their ideas to others. The aims of the study are a) to study the use of inquiry method in learning grammar, and b) to study the effectiveness of using inquiry method with ICT integration in learning subject verb agreement. The pretest and post-test used showed improvement after the treatment using inquiry method given to the students. ICT is also used integrated with the Subject Verb Agreement (SVA) module and inquiry method. From the findings, students are well- exposed to the ICT tools and the appropriate use of ICTs can attract students' attention thus may enhance their performance, students takes ICT as positively to be used in their learning sessions and students show that they have positive attitudes towards English. This study also contributes to the ongoing debate on the use of inquiry method integrated with ICT by using the SVA modules. Key words: Inquiry methods, teaching, grammar, ICT.